Development of Learner Activity Sheets Based on Guided Inquiry to Improve Student Learning Outcomes on Chemical Equilibrium Material - Surastri, Surastri; Agustini, Rudiana (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Education plays an important role in improving the quality of human resources. In the context of implementing the Merdeka Curriculum, teachers are given the freedom to design adaptive and contextual learning processes. Based on preliminary research findings, 50% of students reported difficulties in understanding chemical equilibrium material, with the main obstacles being unfamiliar terminology, excessive memorization, and complex calculations. To address these issues, this study aims to develop guided inquiry-based Learner Activity Sheets on chemical equilibrium material to improve the learning outcomes of class XI high school students. Chemistry learning, especially on the topic of chemical equilibrium, sub-material factors that affect the direction of chemical equilibrium shifts, is often considered abstract and difficult for students to understand, so learning media is needed that can facilitate critical thinking processes and conceptual understanding. Guided inquiry was chosen as a learning approach because it provides a balance between teacher direction and independent exploration by students. The research method used is Research and Development (R&D) with reference to the 4-D development model (Define, Design, Develop, and Disseminate) and limited to the Develop stage only. The population in this study was class XI of IPIEMS Surabaya High School. The results of Learner Activity Sheets validation from the three validators obtained a mode score of 5, which means that Learner Activity Sheets is feasible with very valid categories. The percentage of students' responses obtained was 96% which was declared practical. The learning outcomes of students are declared complete if they reach a score of ≥ 80. Based on the posttest results, the percentage of completeness is 88.5%. This percentage shows that classical completeness has been achieved, so it can be concluded that guided inquiry-based learning is effective in improving student learning outcomes.